OCCURRENCE OF NITROGEN-FIXING CYANOBACTERIA IN LOCAL RICE FIELDS OF ORISSA, INDIA - Dey, H. S.; Tayung, K.; Bastia, A. K. (Ecoprint: An International Journal of Ecology, 2011)
Cyanobacterial diversity occurring in some local rice fields of Orissa, India has been studied in two different seasons and influence of pH, organic carbon (%) and conductivity were correlated on their population. At different locations and seasons the pH of the soil varies from 6.30±0.20 to 6.66±0.305. Conductivity and organic carbon (%) varies from 0.6±0.10 to 0.76±0.152 and 0.56±0.045 to 0.70±0.025 respectively. Altogether 58 taxa belonging to 20 genera were obtained and characterized. Out of these 19 forms were heterocystous and 39 were non-heterocystous. Highest abundance of cyanobacteria was found in order Nostocales which was represented by 15 species. Among the species relative abundance of Oscillatoria chalybea (9.90%) was found to be highest followed by Phormidium purpurascens (8.49%), Cylindrospermum muscicola and Oscillatoria chlorina (8.01%). Highest Shannon's diversity index was recorded in sampling site 1, followed by site 2. Comparatively the diversity index was more during winter than in summer in all the study sites. Highest similarity index (0.174) was found in summer-summer isolates of site 1 and 3. Among the environmental variables (i.e., soil pH, organic carbon (%), conductivity) highly positive correlation was observed between cyanobacterial population and soil pH (r ≥ 9) in all the three sampling sites. The study indicates ubiquitous distribution of cyanobacteria in rice fields and could be exploited for biofertilizer in agriculture. Key words: Cyanobacteria; Rice fields; Abundance; Diversity index; Environmental variables DOI: 10.3126/eco.v17i0.4120 Ecoprint An International Journal of Ecology Vol. 17, 2010 Page: 77-85 Uploaded date: 3 January, 2011